Investigations of the static and dynamic performances of an annular seal with a tilted rotor by transient CFD methods with dynamic mesh - Li, Fengqin; Zhai, Lulu; Cui, Baoling; Zhu, Zuchao; Guo, Jia (Frontiers in Energy Research, 2022)
A transient computational fluid dynamics (CFD) method based on dynamic mesh is adopted to investigate the static and dynamic performances of an annular seal with a tilted rotor. The reliability of the CFD method is verified by the experimental data, and then the variations of dynamic performance and sealing performance under different length-diameter ratios and misalignment angles are investigated by the method. The results show that the leakage flowrate of the tilted annular seal decreases with the increasing length-diameter ratio, while the whirl frequency ratio increases with the length-diameter ratio. The increase of misalignment angle has little detrimental effect on the stability of long shaft system in the three misalignment modes. In addition, the misalignment mode for the tilted position at the half-length of the annular seal can reduce the leakage flowrate.